1972
DOI: 10.1136/jech.26.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic variations in date of last menstrual period of mothers of infants with congenital malformations in South Wales, 1964-66.

Abstract: In a review article on congenital malformations and season of birth, Bailar and Gurian (1965) stated that 'seasonal cycles in births of infants with certain malformations have been demonstrated beyond any reasonable doubt'. Recently, Wehrung and Hay (1970) have referred to the ambiguity of the term 'seasonal ', and Hewitt et al. (1971) (3) secondary-in which the characteristic is associated with season because both characteristic and season are independently related to a certain time of the year (e.g., t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…Cyclie periannual variations in the frequency of hypospadias were found in this study confirming the reports of several authors (6,9,23,24,25). Some authors referred the seasonality of hypospadias to cyclic variations in the hormone status of the mother.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cyclie periannual variations in the frequency of hypospadias were found in this study confirming the reports of several authors (6,9,23,24,25). Some authors referred the seasonality of hypospadias to cyclic variations in the hormone status of the mother.…”
Section: Discussionsupporting
confidence: 92%
“…The minima and maxima, however, seem to differ eonsiderably from country to country. Whereas the maximum ofbirths of children with hypospadias was found to be in April and May in this study, Roberts et al (24,25) reported the maximum in November in England, Neto et al (23) in the last trimester ofthe year in South America, Czeizel et al (9) the same for Hungary and Avelltin (6) a summer maximum in Sweden. The reasons for the differences in the appearance of maxima in different countries remain unclear.…”
Section: Discussionmentioning
confidence: 39%
“…This confirms findings made by many other authors [Carter, 1973;Cassady, 1969;Elwood, 1976;Fedrick, 1976;Frezal et al, 1964;Granroth et al, 1977;Halevi, 1967;Roberts et al, 1972;Wehrung et al, 19701. However, some papers show a higher incidence of malformations in winter [WHO, 19791 and in May [Imaizumi, 19741. According to Sandahl [ 19771, peak incidence for the dates of the mother's last menstrual period were found during February to April for anencephaly, and during July for spina bifida.…”
Section: Seasonal Incidencesupporting
confidence: 93%
“…The most effective means to study seasonality is to perform Edwards' and Hewitt's tests independently ( 11 , 19 ). The results of Hewitt's test should be evaluated under the assumption that no prior hypothesis exists specifying the six-month period of higher expected prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the ‘specific’ tools for detecting seasonality, the use of χ 2 of heterogeneity across k time periods [e.g., 12 months of the year (k=12) in our study] could be considered. However, the power of Edwards' test is higher ( 19 ). This tool was used in the past, but has been abandoned nowadays and, if ever used, it is obligatorily supplemented by a ‘specific’ statistical tool, since the results produced cannot be unequivocally accepted; significant results do not necessarily imply a seasonal pattern, insignificant results cannot rule out a seasonal pattern.…”
Section: Discussionmentioning
confidence: 99%